Factors-4

From Homeworkwiki

Jump to: navigation, search

Factorize :

(i) x 2 + 5 x + 6

(ii) x 2 - 5 x + 6

(iii) x 2 - 5 x - 6

(iv) x 2 + 5 x - 6

Solution :

(i) x 2 + 5 x + 6 = x 2 + 3 x + 2 x + 6 [Since, 3 + 2 = 5 ; and 3 X 2 = 5]

= x (x + 3) + 2 (x + 3)

= (x + 3) (x + 2)

(ii) x 2 - 5 x + 6

x 2 - 3 x - 2 x + 6 [since, ( -3 ) + ( - 2 ) = - 5 ; and ( - 3 ) X ( - 2 ) = + 6]

= x (x - 3) - 2 (x - 3)

= (x - 3) (x - 2)

(iii) x 2 - 5 x - 6 = x 2 - 6 x + x - 6 [Since, - 6 + 1 = - 5 and, ( - 6 ) X 1 = - 6]

= x (x - 6) + 1 (x - 6)

= (x - 6) (x + 1)

(iv) x 2 + 5 x - 6 = x 2 + 6 x - x - 6 [Since, 6 - 1 = 5 and 6 X ( - 1 ) = - 6]

= x (x + 6) - 1 (x + 6)

= (x + 6) (x - 1)

Personal tools
McAfee SECURE sites help keep you safe from identity theft, credit card fraud, spyware, spam, viruses and online scams